2012
DOI: 10.1021/ma300815q
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Supramolecular Extenders with Precise Chain Lengths via Iterative Synthesis and Their Applications in Polyurethane Elastomers

Abstract: In this study, we synthesized a dual-functional building intermediate, 4-(3,3-diethyl-2,4-dioxoazetidin-1-yl)benzoyl chloride (DEDA-BC), from readily available starting materials, including 4-isocyanatobenzoyl chloride and p-tolyl isocyanate. In its iterative syntheses of hard segments, we first treated the highly reactive acid chloride of DEDA-BC with the monoamine (aniline) or the diamine (4,4′-methylenedianiline, 4,4′-MDA) to form first-generation azetidien-2,4-dione intermediates. We then reacted these der… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 40 publications
1
9
0
Order By: Relevance
“…This ultimately conferred an element of shape recovery properties to the material. Further studies have employed supramolecular UPy‐terminated PUs in polymerization‐induced phase separation, whilst a range of other end groups capable of hydrogen bonding interactions have been employed for material assembly …”
Section: Supramolecular Polyurethanesmentioning
confidence: 99%
“…This ultimately conferred an element of shape recovery properties to the material. Further studies have employed supramolecular UPy‐terminated PUs in polymerization‐induced phase separation, whilst a range of other end groups capable of hydrogen bonding interactions have been employed for material assembly …”
Section: Supramolecular Polyurethanesmentioning
confidence: 99%
“…This is the rst thermoplastic polyurethane elastomers with such high thermostability and excellent mechanical properties, compared to the present reported PUs. 7,12,19,50 Furthermore, the comprehensive performance of such pure polyurethane is even superior to many polyurethane-based composite polymers.…”
Section: à3mentioning
confidence: 99%
“…These hard segments act as thermo-reversible physical crosslinking sites providing the characteristic thermoplastic and elastomeric behaviours for TPU. [3] Furthermore, strong evidence has indicated that chain-length and dispersity of molecular weight of hard segments play significant roles in affecting the performance of TPU, such as mechanical and thermal properties [4][5][6][7][8][9] due to the formation of different morphological sizes and crystalline structures. [10][11][12][13][14] TPUs with a narrow dispersity in molecular weight generally show a higher and preferred elastic modulus, a less temperature-dependent modulus between the T g of the soft segment and the T m of the hard segments.…”
Section: Introductionmentioning
confidence: 99%
“…[9,[19][20][21][22][23] Nevertheless, to our knowledge, all the methods reported so far have their drawbacks. Harthcock [20] and his co-workers had to use a cumbersome gel-permeation chromatogram process to isolate individual MDI-butanediol urethane extenders of uniform chain length from random product mixtures to demonstrate their effects.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation